2016
DOI: 10.1007/s10926-016-9670-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Work Participation Across the Life Course

Abstract: Introduction Many disability prevention strategies are focused on acute injuries and brief illness episodes, but there will be growing challenges for employers to manage circumstances of recurrent, chronic, or fluctuating symptoms in an aging workforce. The goal of this article is to summarize existing peer-review research in this area, compare this with employer discourse in the grey literature, and recommend future research priorities. Methods The authors participated in a year-long sponsored collaboration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 90 publications
(101 reference statements)
4
47
0
1
Order By: Relevance
“…The observed reductions in employment and work hours among cancer survivors are speculated to be prompted by lingering physical and mental health effects of cancer and its treatment, changing preferences for work in the aftermath of serious illness, or discrimination on the part of employers (Moran & Short, 2014). Long-term late effects of cancer or its treatment have also been linked to poor work retention among cancer survivors (Carter, 2017;Pransky et al, 2016). Functional impairment is a strong predictor of work ability underpinning the importance of assessing cancer survivors' abilities in relation to employment demands (Moskowitz, Todd, Chen, & Feuerstein, 2014).…”
Section: The Concept Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed reductions in employment and work hours among cancer survivors are speculated to be prompted by lingering physical and mental health effects of cancer and its treatment, changing preferences for work in the aftermath of serious illness, or discrimination on the part of employers (Moran & Short, 2014). Long-term late effects of cancer or its treatment have also been linked to poor work retention among cancer survivors (Carter, 2017;Pransky et al, 2016). Functional impairment is a strong predictor of work ability underpinning the importance of assessing cancer survivors' abilities in relation to employment demands (Moskowitz, Todd, Chen, & Feuerstein, 2014).…”
Section: The Concept Of Workmentioning
confidence: 99%
“…Further research is needed to determine variations in distribution, frequency and importance of employment issues for AYA cancer survivors with differing socio-demographic and clinical characteristics . An Additional study has also been suggested to identify barriers to maintaining work, quality of work life, and career progression as important outcomes in young workers (Pransky et al, 2016). Therefore, the purpose of this research was to explore challenges within workplace interactions and processes while suggesting employment and work environment improvements grounded in narratives from AYA cancer survivors and OHPs.…”
Section: Applying Research To Occupational and Environmental Health Nmentioning
confidence: 99%
“…To achieve this, work has to be transformed to eliminate the factors that demotivate older workers to stay in or enter the labor market [ 16 , 17 ]. Concerns about the work sustainability, including the economic growth, pensions, and labour supply, have motivated a policy response as a potential solution to address the issues of longer working lives and later retirement [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Public and private policies aimed at inclusion also have made a difference, such as through governmental implementation of disability antidiscrimination laws [5] and private sector efforts related to inclusive corporate cultures [6]. Occupational rehabilitation professionals' contributions to improving inclusion likewise include advances in on-the-ground and micro-level programs, such as return-to-work and workplace injury-prevention programs [7,8].Despite this positive momentum, research continues to show that such advances have not eliminated the significant disparities in economic and community participation between people with and without disabilities; for example, in the United States, labor force participation rates for people with disabilities still stand at 21% as compared to 69% for people without disabilities [9], and essential avenues to community engagement and civic participation lag [10].Abstract Purpose From an array of disciplinary perspectives, the articles in this special section examine opportunities and challenges in the economic, social, and civic participation of individuals across the spectrum of disabilities. Methods At multiple levels of analysis, the contributors consider employment law and policy frameworks, occupational and vocational rehabilitation strategies, and corporate practices in support of the full and equal inclusion of people with disabilities in society.…”
mentioning
confidence: 99%
“…Public and private policies aimed at inclusion also have made a difference, such as through governmental implementation of disability antidiscrimination laws [5] and private sector efforts related to inclusive corporate cultures [6]. Occupational rehabilitation professionals' contributions to improving inclusion likewise include advances in on-the-ground and micro-level programs, such as return-to-work and workplace injury-prevention programs [7,8].…”
mentioning
confidence: 99%